Effectiveness of culturally tailoring smoking cessation interventions for reducing or quitting combustible tobacco: a systematic review and meta-analyses - Leinberger-Jabari, A; Golob, MM; Lindson, NL; Hartmann-Boyce, J (Wiley, 2023)
Background and Aims: Standard approaches to smoking cessation may not be as effective for certain populations, and tailoring on cultural factors could improve their effectiveness. This systematic review measured the effectiveness of culturally tailoring smoking cessation interventions on quitting or reducing smoking combustible tobacco. Method: We searched MEDLINE, PsychInfo, Embase and Cochrane Central Register from inception to 21 June 2023 for randomized controlled trials (RCTs) of community-based, primary care or web-based interventions for smoking cessation in adults who smoked tobacco, with measurement of smoking abstinence or reduction at least 3 months following baseline. We examined comparisons between either an intensity-matched culturally tailored intervention and a non-tailored intervention or a standard non-tailored intervention and the same intervention plus a culturally tailored adjunct. We sub-grouped studies according to the level of tailoring and performed subgroup analyses where appropriate. We assessed risk of bias and certainty of evidence. Results: We identified 43 studies, 33 of which were meta-analyzed (n = 12 346 participants). We found moderate certainty evidence, limited by heterogeneity, that intensity-matched culturally tailored cessation interventions increased quit success when compared with non-tailored interventions at 3-month follow-up or longer (n = 5602, risk ratio [RR] = 1.29 95% confidence interval [CI] 1.10, 1.51, I2 = 47%, 14 studies). We found a positive effect of adding a culturally tailored component to a standard intervention compared with the standard intervention alone (n = 6674, RR = 1.47, 95% CI 1.10, 1.95, I2 = 74%, 18 studies), but our certainty in this effect was low due to imprecision and substantial statistical heterogeneity. Conclusion: Culturally tailored smoking cessation interventions may help more people to quit smoking than a non-tailored intervention. Adapting or adding cultural components to smoking cessation interventions originally developed for majority populations could improve cessation rates in populations who do not fully identify with majority cultural norms.